The sanctity of rural life : nobility, protestantism, and nazism in Weimar Prussia - Baranowski, Shelley 1946- (Oxford Univ. Press, 1995)
In The Sanctity of Rural Life: Nobility, Protestantism, and Nazism in Weimar Prussia, Shelley Baranowski explores how and why the rural population of eastern Prussia turned to Nazism in large numbers. She explains the role of the rural elite and the church in propagating a myth of the stability, the wholesomeness, and the class-harmony - in short, the "sanctity" - of rural life that encouraged the spread of Nazism. This study identifies the contributions of the rural elite in the eastern Prussian provinces, namely Junker landlords and the Protestant clergy, to the rise of National Socialism in a region where the rural electorate's attraction to the Hitler movement became critical to the Nazi takeover in 1933. Using the province of Pomerania as a primary example, Baranowski argues that rather than emerging strictly as a protest against the domination of elites, as is regularly suggested, the Nazis had to address issues that rural elites defined in order to establish a foothold among rural voters. The most significant issue was the conviction that the urban bias of the Weimar Republic threatened the survival of the rural economy and culture. Despite the social tensions that surfaced periodically, the anti-republicanism which united all rural classes encouraged rural dwellers to turn to Nazism as the salvation of rural society. This ground-breaking work makes a major contribution to our understanding of Protestant and rural support for Nazism and adds an important cultural and religious dimension to our understanding of the underpinnings of Nazi power. It will be of interest to historians and students of modern European and German history.